Gender, Religion and Grassroots Development in Nigeria : Diagraming the Role of the Federation of Muslim Women Associations (FOMWAN) and the Christian Zumuntar Mata - Bunza, Mukhtar Umar; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2025)
This study revisits and explores the contributions of women religious organizations in Nigeria, namely, The Federation of Muslim Women Organizations in Nigeria, (FOMWAN) and Zumuntar-Mata (Church Women League) of Christian Churches, in comparative and proportional evaluations. The elemental findings reveal that these religious organizations under study are well structured and methodical associations with the primary aim of addressing some major challenges faced by women in Nigeria, and had taken necessary steps to ameliorate them. Initiatives such as Economic empowerment, educational, religious and political enlightenments, and provision of health services are their major contributions to women and the society at large. One interesting manifestation of toleration among the two differing religious groups was that they cooperate and, in some cases, jointly execute some essential and enablement programs to both Muslim and Christian women. Their slogans ‘the act of kindness knows no boundary’ is always at fore. In the same vein, in order to widen the horizon of their activities and responsibilities they partner favorably and mutually with development partners governmental and non-governmental within Nigeria and beyond with a bid to advance and extend their interventions to as many women as possible in the cities as well as in the rural areas. Through their various programs and initiatives for self-help, therefore, the organizations significantly contributed towards women enfranchisement and impacted in societal development positively.
Keywords: Gender; Religion; Development; FOMWAN; Zumuntar-Mata; Nigeria